Protest Movements Against Sanctuaries in Odisha: Politics with Other Means. (November 2021) - Ray, Sthitapragyan
This study seeks to counter interpretations of tribal movements as reflecting parochial and perverse ethno-territorial aspirations, mostly in irrational violent forms. It compares two peaceful protest movements against wildlife sanctuaries located in different geographical and political-economic settings in the eastern Indian state of Odisha. As rational collective actions, both movements relied on the agency of project-affected persons who questioned state attempts to de-politicise development in the name of scientific conservation. The study shows how the legitimate concerns of such project-affected citizens were overshadowed by politics and the context-specific dialectical interface between three different factors, namely availability of indigenous organisational resources, political opportunity structures and identity construction.